2010
DOI: 10.1155/2010/503817
|View full text |Cite
|
Sign up to set email alerts
|

Recent Visual Decline—A Health Hazard with Consequences for Social Life: A Study of Home Care Clients in 12 Countries

Abstract: Information about recent visual decline (RVD) and its consequences is limited. The aim was to investigate this in an observational, prospective study. Participants were recipients of community home services, ≥65 years, from Ontario (Canada, n = 101618), Finland (the-RAI-database, STAKES, n = 1103), and 10 other European countries (the-Aged-in-HOmeCarestudy (AdHOC), n = 3793). The instrument RAI-HC version 2.0 was used in all sites. RVD was assessed by the item “Worsening of vision compared to status 90 days ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…The relationship persists, however, after adding past MDE to the final model. This observation suggests that a recent decrease in visual function may be more important in relation to depressive symptomatology than a sustained moderately low level, in the same way that Grue et al (Grue et al, 2010) observed recent decline rather than stable impairment led to IADL impairment and declining social activity.…”
Section: Vision Loss As a Risk Factor For Depressive Symptomatologymentioning
confidence: 67%
See 1 more Smart Citation
“…The relationship persists, however, after adding past MDE to the final model. This observation suggests that a recent decrease in visual function may be more important in relation to depressive symptomatology than a sustained moderately low level, in the same way that Grue et al (Grue et al, 2010) observed recent decline rather than stable impairment led to IADL impairment and declining social activity.…”
Section: Vision Loss As a Risk Factor For Depressive Symptomatologymentioning
confidence: 67%
“…Rates of visual impairment in the elderly increase with age and are not only associated with significant functional loss and mortality (Berger and Porell, 2008;Grue et al, 2010;Jacobs et al, 2005;Laitinen et al, 2007) but also engender considerable psychological distress. Visual impairment has been observed notably to lead to an increased sense of loneliness (Heikkinen and Kauppinen, 2004;Jacobs et al, 2005) and increased rates of clinically significant levels of depressive symptomatology.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst some people with vision impairment live fulfilled, independent lives despite significant impairment, others have a poor quality of life, even with lesser degrees of impairment (Hernandez Trillo & Dickinson, 2012; population there is considerable variation in wellbeing and physical and mental health (McManus & Lord, 2012). Vision impairment has multi-faceted impacts upon people's lives; it impacts on functional ability and mobility (both in terms of getting out and about and individual functional mobility), which affects social interaction and psychological wellbeing (Gallagher, Hart, O'Brien, Stevenson, & Jackson, 2011;Grue et al, 2010;Hodge & Eccles, 2013). However, the relationship between severity of impairment and the impact upon wellbeing is not simple (Schilling, Wahl, Horowitz, Reinhardt, & Boerner, 2011); there is a range of influencing factors (Brown & Barrett, 2011).Hernandez Trillo & Dickinson (2012) found non-visual factors including physical and mental health to be better predictors of quality of life in people with a vision impairment than visual function, whilst Tabrett and Latham (2012) reported that personality traits influenced the occurrence of depression in vision impaired people.…”
Section: Introductionmentioning
confidence: 99%
“…Fear of falling (FoF), with or without a fall, is also common in VIOP and can lead to a cycle of restricting daily activity and mobility, loss of confidence, diminishing physical and mental assets and reduced social participation and overall QoL. [28][29][30] A UK report by Visibility, a Glasgow-based vision charity, found that older people are highly likely to avoid activity because of VI. 31 Anxiety and depression are also common in those with VI and this may also lead to reduced activity.…”
Section: Fear Of Falling and Visual Impairmentmentioning
confidence: 99%